Platform opening and cooperation: A literature review and research agenda - Weihua Liu; Yanjie Liang; Xiaoran Shi; Peiyuan Gao; Li Zhou (Modern Supply Chain Research and Applications, 2022)
Purpose - The review aims to facilitate a broader understanding of platform opening and cooperation and points out potential research directions for scholars. Design/methodology/approach - This study searches Web of Science (WOS) database for relevant literature published between 2010 and 2021 and selects 86 papers for this review. The selected literature is categorized according to three dimensions: the strategic choice of platform opening and cooperation (before opening), the construction of an open platform (during opening) and the impact of platform opening and cooperation (after opening). Through comparative analysis, the authors identify research gaps and propose four future research agendas. Findings - The study finds that the current studies are fragmented, and a research system with a theoretical foundation has not yet formed. In addition, with the development of platform operations, new topics such as platform ecosystems and open platform governance have emerged. In short, there is an urgent need for scholars to conduct exploratory research. To this end, the study proposes four future research agendas: strengthen basic research on platform opening and cooperation, deeply explore the dynamic evolution and cutting-edge models of platform opening and cooperation, analyze potential crises and impacts of platform openness and strengthen research on open platform governance. Originality/value - This is the first systematic review on platform opening and cooperation. Through categorizing literature into three dimensions, this article clearly shows the research status and provides future research avenues.
Keywords: 650; Co-opetition; Platform cooperation; Platform opening; Research agenda